Mucoepidermoid Carcinoma of the Breast With MAML2 Rearrangement: A Case Report and Literature Review. (October 2020) - Yan, Mingfei; Gilmore, Hannah; Harbhajanka, Aparna
Mucoepidermoid carcinoma is one of the most common malignancies in salivary glands. In comparison, breast mucoepidermoid carcinoma is a very rare entity, with limited reports and understanding of its clinical behaviors to date. In this article, we report a case of low-grade breast mucoepidermoid carcinoma of a 60-year-old female patient. Histologic and immunohistochemical patterns were demonstrated. Fluorescence in situ hybridization test was also conducted to identify MAML2 rearrangement in this case, indicating a similar molecular abnormality as mucoepidermoid carcinoma in the salivary gland. Five-year follow-up of the patient showed no local recurrence or distant metastasis of the carcinoma, indicating the indolent behavior of low-grade breast mucoepidermoid carcinoma. Besides, a 40-year literature review from 1979 to 2019 was also performed to better characterize the prognosis and molecular abnormalities of the lesion.